Distinct right frontal lobe activation in language processing following left hemisphere injury. - Voets, N; Adcock, J; Flitney, D; Behrens, T; Hart, Y; Stacey, R; Carpenter, K; Matthews, P (2006)
Right hemisphere activation during functional imaging studies of language has frequently been reported following left hemisphere injury. Few studies have anatomically characterized the specific right hemisphere structures engaged. We used functional MRI (fMRI) with verbal fluency tasks in 12 right-handed patients with left temporal lobe epilepsy (LTLE) and 12 right-handed healthy controls to localize language-related activity in the right inferior frontal gyrus (RIFG). During the phonemic task, LTLE patients activated a significantly more posterior region of the right anterior insula/frontal operculum than healthy controls (P = 0.02). Activation of the left inferior frontal gyrus (LIFG) did not differ significantly between the two groups. This suggests that, following left hemisphere injury, language-related processing in the right hemisphere differs from that with a functionally normal left hemisphere. The localization of activation in the left and right inferior frontal gyri was determined with respect to the anatomical sub-regions pars opercularis (Pop), pars triangularis (Ptr) and pars orbitalis (Por). In the LIFG, both healthy controls (8 out of 12) and LTLE patients (9 out of 12) engaged primarily Pop during phonemic fluency. Activations in the RIFG, however, were located mostly in the anterior insula/frontal operculum in both healthy controls (8 out of 12) and LTLE patients (8 out of 12), albeit in distinct regions. Mapping the locations of peak voxels in relation to previously obtained cytoarchitectonic maps of Broca's area confirmed lack of homology between activation regions in the left and right IFG. Verbal fluency-related activation in the RIFG was not anatomically homologous to LIFG activation in either patients or controls. To test more directly whether RIFG activation shifts in a potentially adaptive manner after left hemisphere injury, fMRI studies were performed in a patient prior to and following anatomical left hemispherectomy for the treatment of Rasmussen's encephalitis. An increase in activation magnitude and posterior shift in location were found in the RIFG after hemispherectomy for both phonemic and semantic tasks. Together, these results suggest that left temporal lobe injury is associated with potentially adaptive changes in right inferior frontal lobe functions in processing related to expressive language.